Analisis Kebutuhan Media Pembelajaran E-Booklet Bermuatan Konservasi Orangutan Tapanuli (Pongo tapanuliensis) Sebagai Suplemen Pembelajaran Biologi di SMAN 4 Padang: Penelitian - Hidayat, Fathurrahman; Muhyiatul Fadilah; Fajrina, Suci; Rahmi, Fitri Olvia (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The use of e-booklet media with Orangutan conservation content can provide deeper knowledge of conservation and can also add variety to biology learning, so as to increase students' awareness of animal and environmental conservation. This study aims to describe the need to develop electronic-based learning media with Orangutan Tapanuli conservation content as a learning supplement at SMAN 4 Padang. This study uses a descriptive qualitative approach method, which involves collecting qualitative data and providing descriptive explanations. The research instruments are in the form of interview sheets with biology teachers and student questionnaires. The subjects of this study were 35 students of class X E 6 and Biology teachers at SMAN 4 Padang. Based on the results of the study, 85.7% of students agreed to use e-booklet learning media in learning. On the other hand, 91.4% of students also need conservation-based learning to increase their knowledge.